Evaluation of the nutrition and health status of pregnancy according to the severity of emezis - Altın Bayar, Ekin; Tazeoğlu, Aybala; Kuyulu Bozdoğan, Fatma Bengü (Acıbadem Mehmet Ali Aydınlar University, 2022)
Objective: Gestational emesis affects the whole pregnancy process and the newborn baby after pregnancy, starting from the early stages of pregnancy. In this study, it was aimed to investigate the factors affecting gestational emesis. Materials-Methods: This study evaluated the relationship between the severity of nausea-vomiting and nutrition and health status of 100 pregnant women aged 18-40 years who applied to the Nutrition-Diet and Gynecology Clinic in a private hospital. Results: The mean age of the participants was 29.66±5.47. It was determined that the severity of vomiting increased as the number of pregnancies of the participants increased (p<0.05). It was determined that as the severity of vomiting increased, the energy intake averages of the pregnant women decreased significantly. Those with 'severe' emesis were found to be significantly lower than those with 'moderate' emesis, which derived most of their energy from carbohydrates and fats (p=0.002, p=0.02, respectively). Conclusion: Many underlying factors affect the severity of vomiting in pregnant women. The increase in the severity of vomiting adversely affects the nutritional and health status of pregnant women. For this reason, the severity of nausea and vomiting should be taken into account in ensuring proper nutrition and improving health conditions in pregnant women.

Amaç: Gestasyonel emezis, gebeliğin erken dönemlerinden başlayarak tüm gebelik sürecini ve gebelik sonrası yeni doğan bebeği etkiler. Bu çalışmada gestasyonel kusmayı etkileyen faktörlerin araştırılması amaçlandı. Gereç-Yöntem: Bu çalışmada, özel bir hastanede Beslenme-Diyet ve Kadın Hastalıkları Kliniği’ne başvuran 18-40 yaş arası 100 gebenin bulantı-kusma şiddeti ile beslenme ve sağlık durumu arasındaki ilişki değerlendirildi. Bulgular: Katılımcıların yaş ortalaması 29.66±5.47 idi. Katılımcıların gebelik sayısı arttıkça kusma şiddetinin arttığı belirlendi (p<0.05). Kusma şiddeti arttıkça gebelerin enerji alım ortalamalarının önemli ölçüde düştüğü belirlendi. ‘Şiddetli’emezisi olanlar, enerjisinin çoğunu karbonhidrat ve yağlardan alan ‘orta’emezisi olanlara göre anlamlı derecede daha düşük bulundu (sırasıyla p=0.002, p=0.02). Sonuç: Gebe kadınlarda kusmanın şiddetini birçok altta yatan faktör etkiler. Kusmanın şiddetinin artması gebelerin beslenme ve sağlık durumlarını olumsuz etkiler. Bu nedenle gebelerde doğru beslenmenin sağlanması ve sağlık koşullarının iyileştirilmesinde bulantı ve kusmanın şiddeti dikkate alınmalıdır.
Gebelerde beslenme ve sağlık durumunun emezis şiddetine göre değerlendirilmesi
Keywords: Pregnancy; Hyperemesis Gravidarum; Nutritional Status; Gebelik; Hiperemezis Gravidarum; Beslenme Durumu